Anti-spike S1 IgA, anti-spike trimeric IgG, and anti-spike RBD IgG response after BNT162b2 COVID-19 mRNA vaccination in healthcare workers: IgG and IgA response after BNT162b2 mRNA vaccination - Salvagno, Gian Luca; Henry, Brandon; Di Piazza, Giovanni; Pighi, Laura; De Nitto, Simone; Bragantini, Damiano; Gianfilippi, Gianluca; Lippi, Giuseppe (Journal of Medical Biochemistry, 2021)
Background: Most studies on immune response after coronavirus disease 2019 (COVID-19) vaccination focused on serum IgG antibodies and cell-mediated immunity, discounting the role of anti-SARS-CoV-2 neutralizing IgA antibodies in preventing viral infection. This study was aimed to quantify serum IgG and IgA neutralizing antibodies after mRNA COVID-19 vaccination in baseline SARS-CoV-2 seronegative healthcare workers. Methods: The study population consisted of 181 SARS-CoV-2 seronegative healthcare workers (median age 42 years, 59.7% women), receiving two doses of Pfizer COVID-19 vaccine BNT162b2. Serum samples were collected before receiving the first vaccine dose, 21 days (before the second vaccine dose) and 50 days afterwards. We then measured anti-spike trimeric IgG (Liaison XL, DiaSorin), anti-spike receptor binding domain (RBD) IgG (Access 2, Beckman Coulter) and anti-spike S1 subunit IgA (ELISA, Euroimmun). Results were presented as median and interquartile range (IQR). Results: Vaccine administration elicited all anti-SARS-CoV-2 antibodies measured. Thirty days after the second vaccine dose, 100% positivization occurred for anti-spike trimeric IgG and anti-spike RBD IgG, whilst 1.7% subjects remained anti-spike S1 IgA negative. The overall increase of antibodies level over baseline after the second vaccine dose was 576.1 (IQR, 360.7-867.8) for anti-spike trimeric IgG, 1426.0 (IQR, 742.0-2698.6) for anti-spike RBD IgG, and 20.2 (IQR, 12.5-32.1) for anti-spike S1 IgA. Significant inverse association was found between age and overall increase of anti-spike trimeric IgG (r=-0.24; p=0.001) and anti-spike S1 IgA (r=-0.16; p=0.028), but not with anti-spike RBD IgG (r=-0.05; p=0.497). Conclusions: mRNA COVID-19 vaccination elicits sustained serum levels serum anti-spike trimeric IgG and anti-spike RBD IgG, while also modestly but significantly increasing those of serum anti-spike S1 IgA.